Characterization of Lipid Compounds of the Dried Fruits of Xylopia aethiopica (Dunal) A. Rich Growing in Sudan - Elhassan, Itmad Awad; Elmubarak, Elsiddig Elamin; Ayoub Hussein, Saad Mohamed (Pakistan Journal of Nutrition, 2009)
Total lipids extracted from the seeds of X. aethiopica were found to be 10%. The oil was analyzed for fatty acids and sterols composition. Thirteen fatty acids were identified, with their methyl esters using GC/MS analytical method. The majority of fatty acids were unsaturated (72%). Oleic acid was the dominant unsaturated fatty acid (69.37%), while the saturated fatty acids represented about 27% of the total fatty acids present in oil from seeds, mainly palmatic acid (15.66%) and stearic acid (9.5 %). The sterols quantification and identification were preformed by analysis of the unsaponifiable matter of the seed oil using GC/MS technique. The level of sterols estimated in the oil was 4.2 g/kg oil. The main component was Sitosterol which represented about 58% of the total sterol content, followed by campesterol (23.5%) and Δ5-Avenasterol (12.1%). Cholesterol was found at about 3% of total sterols.